SYSTEM OF INDICATORS FOR MONITORING THE ECONOMIC SECURITY IN THE REGION - I. Е. Denezhkina (Real Economics Publishing House, 2014)
This article describes the process of designing system to minimize risks in order to construct the algorithm for monitoring, analyzing and evaluating the economic security in the region. The approach to the selection of economic security indicators is justified. For each indicator relevant thresholds values are identified and substantiated. The indicators system allows determining the reproduction processes vector in which the risks of internal and external threats to social and economic development in the region minimize.